The cytokinin-producing plant beneficial bacterium Pseudomonas fluorescens G20-18 primes tomato (Solanum lycopersicum) for enhanced drought stress responses - Mekureyaw, Mengistu F; Pandey, Chandana; Hennessy, Rosanna C; Nicolaisen, Mette H; Liu, Fulai; Nybroe, Ole; Roitsch, Thomas (Journal of plant physiology, 2022)
Plant growth-promoting rhizobacteria (PGPR) are known for exerting beneficial effects on plant growth and tolerance to plant pathogens. However, their specific role in mediating protection against abiotic stress remains underexplored. The aim of this study was to characterise the ability of the cytokinin-producing beneficial bacterium Pseudomonas fluorescens G20-18 to enhance tomato growth and boost tolerance to drought stress. Tomato seedlings were root inoculated and their growth and physiological and molecular responses assessed under well-watered conditions and also in response to progressive drought stress and a subsequent recovery period. Root inoculation with G20-18 had a significant positive impact on tomato growth. Furthermore, G20-18 inoculated and drought-stressed plants showed higher leaf chlorophyll and abscisic acid (ABA) content and stomatal closure than non-inoculated controls. Root inoculation also increased the activity of different carbohydrate metabolism enzymes, which are important for root and leaf growth and development in drought stressed plants. A significant increase in the activity of different antioxidant enzymes and total antioxidant capacity correlated with elevated levels of relevant secondary metabolites, such as phenolics, anthocyanins and flavonoids. RNA sequencing revealed distinct qualitative and quantitative differences in gene regulation in response to G20-18. Notably, the number of genes differentially regulated in response to G20-18 was approximately sevenfold higher during drought stress, indicating that root inoculation with the bacteria primed the plants for a much stronger transcriptionally regulated systemic drought stress response. The regulated genes are related to phenylalanine metabolism and other key processes linked to plant growth, development and drought stress resilience. A role of the ability of G20-18 to produce the plant hormone cytokinin for interaction with tomato was established by the cytokinin-deficient biosynthesis mutants CNT1 and CNT2. In comparison with G20-18, the inoculation of plants with CNT1 resulted in a reduced number of differentially regulated genes. The relative change was most prominent under well-watered conditions with a 85 % reduction, corresponding to 462 genes. However, under drought conditions the absolute number of differentially regulated genes was reduced by even 2219 in response to the CNT1 mutant. The relevance of the ability of G20-18 to produce cytokinins for interaction with plants was also evident from differences in growth and specific cell and ecophysiological parameters in response to CNT1 and CNT2. These findings provide novel insights about G20-18's ability to improve drought stress responses and the role of interkingdom signalling by bacterial-derived cytokinins, and contribute to enhance the robustness of the practical application of these microorganisms to improve crop resilience in agricultural production.
Keywords: Plant growth-promoting rhizobacteria (PGPR); P. fluorescens; Drought stress; Transcriptome analyses; Carbohydrate and antioxidant metabolism